ROLE OF FAT TALK ON THE RELATIONSHIPS IN THE BRUNEIAN CHINESE SOCIETY - Khoo, Shee Ping; Lee, Brice Tseen Fu (UI Scholars Hub, 2024)
This research paper examines the role of “fat talk” in relationships in Bruneian Chinese society. “Fat talk” refers to negative comments about one's weight or body shape towards oneself or others. Using qualitative research methods, the study explores the perceptions and experiences of Bruneian Chinese individuals regarding “fat talk”, factors leading to the discussion of the topic, and its impact on their relationships with their peers. The findings suggest that while “fat talk” is prevalent in Bruneian Chinese society, it can have both positive and negative effects on relationships. The study aims to highlight the importance of addressing the “fat talk” issue in Bruneian Chinese society to promote body positivity and healthy communication in relationships.